3D Land Administration for 3D Land Uses. (November 2020) - van Oosterom, Peter; Bennett, Rohan; Koeva, Mila; Lemmen, Christiaan
Highlights: Motivation for research in the domain of 3D Land Administration Explanation on terminology 3D Cadastres - 3D Land Administration FIG 3D Cadastres 2018 Workshop as initial start of the papers in the special issue Role of ISO 19152 LADM, and its revision in the context of 3D Land Administration Short introduction to each of the sixteen papers in the special issue